Advances in Chemistry of 2-(Piperazin-1-yl) Quinoline (Part IV) - El-Bana, Ghada G.; Gouda, Moustafa A. (Mini-Reviews in Organic Chemistry, 2024)
This review described the preparation of 2-(piperazin-1-yl) quinoline derivatives from 2- haloquinolines and anilides, which underwent alkylation, arylation, acylation, and reductive amination to form the 2-piprazinoquinolines. 2-(Piperazin-1-yl) quinoline used as building blocks for the synthesis of polyfunctionalized heterocyclic compounds with pharmacological interest.
Keywords: alkylation